2019
DOI: 10.1007/s12671-019-01284-7
|View full text |Cite
|
Sign up to set email alerts
|

Bolstering Cognitive Resilience via Train-the-Trainer Delivery of Mindfulness Training in Applied High-Demand Settings

Abstract: Objectives Mindfulness training (MT) guidelines recommend that trainers have familiarity and knowledge of the training group as well as extensive MT expertise. Herein, a "train-the-trainer" (TTT) dissemination model was investigated for military service members whose access to MT is threatened by a scarcity of qualified trainers. Methods US Army Master Resilience Trainer-Performance Experts (PEs), who had extensive familiarity with soldiers but no prior MT experience, participated in an MT practicum, and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 40 publications
(73 reference statements)
1
31
0
1
Order By: Relevance
“…Some studies demonstrating improved cognition have modified MBPs to address the needs of a specific population, like the Mindfulness-based mind fitness training course developed to address the specific needs of the military (Jha et al, 2010(Jha et al, , 2015 or the Mindfulness-oriented recovery enhancement program which focuses on addiction, opioiddependent and chronic pain populations Garland et al, 2017). A number of non-RCT studies have now shown improvements in working memory using the operation span task (Jha et al, 2010), or a lack of degradation of sustained attention, inhibitory control capacity and working memory in military cohorts following Mindfulnessbased mind fitness training (Jha et al, 2015(Jha et al, , 2017(Jha et al, , 2020. Participants randomized to Mindfulness-oriented recovery enhancement exhibited significantly reduced attentional bias in comparison to active controls Garland et al, 2017).…”
Section: Complementary Lines Of Evidencementioning
confidence: 99%
“…Some studies demonstrating improved cognition have modified MBPs to address the needs of a specific population, like the Mindfulness-based mind fitness training course developed to address the specific needs of the military (Jha et al, 2010(Jha et al, , 2015 or the Mindfulness-oriented recovery enhancement program which focuses on addiction, opioiddependent and chronic pain populations Garland et al, 2017). A number of non-RCT studies have now shown improvements in working memory using the operation span task (Jha et al, 2010), or a lack of degradation of sustained attention, inhibitory control capacity and working memory in military cohorts following Mindfulnessbased mind fitness training (Jha et al, 2015(Jha et al, , 2017(Jha et al, , 2020. Participants randomized to Mindfulness-oriented recovery enhancement exhibited significantly reduced attentional bias in comparison to active controls Garland et al, 2017).…”
Section: Complementary Lines Of Evidencementioning
confidence: 99%
“…As scheduling active-duty cohorts can be challenging, this methodology is consistent with other military studies (e.g. Adler et al, 2008;Jha et al, 2020). Personal identifying information was removed from the…”
Section: The Present Studymentioning
confidence: 99%
“…Because such time requirements can be prohibitively burdensome for time-pressured groups, there is growing interest in determining the effectiveness of short-form MT in non-clinical settings as a route by which to promote cognitive functioning and psychological well-being (Creswell, 2017). Short-form MT has been found to benefit cognitive functions in a variety of time-pressured, high-demand groups from undergraduate students (Morrison et al, 2014;Mrazek et al, 2013) and athletes (Rooks et al, 2017) to first responders (Denkova et al, 2020) and military service members (Jha et al, 2020;Zanesco et al, 2019). For many of these groups, greater engagement in mindfulness practice corresponds with greater cognitive benefits (Denkova et al, 2020;Rooks et al, 2017;Zanesco et al, 2019).…”
mentioning
confidence: 99%
“…A recent study examined the effectiveness of short-form MT delivered by professional mental skills trainers, with significant military context familiarity but no prior experience with MT. Using a "train-the-trainer" approach (Jha et al, 2020), mindfulness-naïve, context-familiar trainers were offered a 12-week practicum to gain first-person familiarity with mindfulness practices and concepts, as well as to achieve proficiency in delivering a short-form MT program contextualized for soldiers. Compared to soldiers who received no training as well as those who received the same MT program delivered by a mindfulness expert who lacked military familiarity, those trained by the context-familiar trainers demonstrated protective effects in cognitive functioning (i.e., sustained attention and working memory).…”
mentioning
confidence: 99%
See 1 more Smart Citation